PERSEPSI REMAJA TENTANG DAMPAK PERILAKU SEKSUAL PRA NIKAH - Kuhon, Micha V.Z; Rakinaung, Natalia; Tiwatu, Filia V. (Lasalle Health Journal, 2024)
Introduction: Sexual Behavior is any action motivated by the desire to engage in sexual activity, either with the same or opposite sex. Adolescent sexual behavior can have a negative impact on their body, mind, and social relationships. Based on the facts in the field there are 3-4 students who experience the impact of adolescent sexual behavior, namely premarital pregnancy in 2022, not including in previous years. Objective: This study aims to explore adolescents' perceptions of the impact of premarital sexual behavior on adolescents. Method: e design of this research was qualitative descriptive research. The population is all students who were in class XI. The number of samples is 7 students of class XI. Results: The results of thematic analysis regarding adolescents' perceptions of the impact of premarital sexual behavior that sexual behavior has adverse effects on the body, changes to the body, physical health, hormones, and puberty. There are also emotional and psychological. Conclusions: Adolescents have the perception that premarital sexual behavior has adverse effects on physical, emotional, psychological, as well as relationships with society and family, but peers remain supportive of adolescents who have done so. Adolescents also felt that they were not given sexual education by their parents, and they wanted to gain access to more information about the impact of sexual behavior